Development and validation of a new set-up simulator dedicated to ocular proton therapy at CNAO. (February 2021) - Elisei, G.; Pella, A.; Ricotti, R.; Via, R.; Fiore, M.R.; Calvi, G.; Mastella, E.; Paganelli, C.; Tagaste, B.; Bello, F.; Fontana, G.; Meschini, G.; et al.
Highlights: Non-dedicated line OPT requires challenging and time-demanding set-up preparation. A simulator for patient-specific setup virtualization and optimization is proposed. New approach validation is based on geometric data of 30 patients treated in CNAO. Treatment requirements, both clinical and geometric are met. Clinical impact in terms of time-demand and patient safety. Abstract: An Eye Tracking System (ETS) is used at CNAO for providing a stable and reproducible ocular proton therapy (OPT) set-up, featuring a fixation light (FL) and monitoring stereo-cameras embedded in a rigid case. The aim of this work is to propose an ETS set-up simulation algorithm, that automatically provides the FL positioning in space, according to patient-specific gaze direction and avoiding interferences with patient, beam and collimator. Two configurations are provided: one in the CT room for acquiring images required for treatment planning with the patient lying on a couch, and one related to the treatment room with the patient sitting in front of the beam. Algorithm validation was performed reproducing ETS simulation (CT) and treatment (room) set-up for 30 patients previously treated at CNAO. The positioning accuracy of the device was quantified through a set of 14 control points applied to the ETS case and localizable both in the CT volume and in room X-ray images. Differences between the position of ETS reference points estimated by the algorithm and those measured by imaging systems are reported. The corresponding gaze direction deviation is on average 0.2° polar and 0.3° azimuth for positioning in CT room and 0.1° polar and 0.4° azimuth in the treatment room. The simulation algorithm was embedded in a clinically usable software application, which we assessed as capable of ensuring ETS positioning with an average accuracy of 2 mm in CT room and 1.5 mm in treatment room, corresponding to gaze direction deviations consistently lower than 1°.